Researcher understanding of food innovations in Nordic and Southern European countries: A systematic literature review. (July 2018) - Savino, Tommaso; Testa, Stefania; Messeni Petruzzelli, Antonio
Abstract: Background: The capability of agro-food firms to innovate positively influences their profits and growth. Accordingly, the literature has tried to comprehend innovation phenomena occurring within the agri-food industry which generates high levels of economic output and employment in the European Union. Nonetheless, innovation in the food industry is deeply affected by cultural heritage, habits, and institutional contexts. Europe's considerable cultural variation causes different innovations in different regions. The most evident disparities in food cultures and gastronomic approaches have been observed between Nordic and Southern European countries. Despite ample interest in comparing these two European areas, few studies in the food innovation literature have adopted a comparative approach. Scope and approach: The authors aim to identify the main research streams that study food innovations in Nordic and Southern European countries, as well as the results provided by researchers. To achieve these objectives, we conducted a systematic literature review of 67 articles in the food innovation field. Key findings and conclusions: The review recognises six main research streams along which the academic literature has organised its debate: innovation acceptance, innovation policy initiatives, innovation networks, innovation in traditional food products, alternative food systems, and convention theory. The authors discuss the results emerging from each research stream and also the different patterns that emerge in the literature between Nordic and Southern countries of Europe. Highlights: Literature on Southern European countries is mainly focused on innovation acceptance. Literature on Nordic countries is mainly focused on policy initiatives. Agents, media, and socio-demographic characteristics affect food innovation acceptance. New innovation policies follow more socially distributed and transdisciplinary models. Southern European food market seems more prone to accept changes regarding TFPs.